The Impact Of Carbon Emission Disclosure On The Value Of Companies With Foreign Ownership As A Moderation Variable - Angela Lionika; Wahdan Arum Inawati (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The entire industry in the company seeks to grow the economy in the future and wants to achieve an increase in investment and productivity so as to get maximum profit. These advantages become the attraction of an investor to the value of the company to make an investment that investors will pay attention to. This research was conducted with the aim of knowing the effect of carbon emission disclosure proxied by (GRI) with the control variable company size (Ln), profitability (ROA) and leverage (DER) and foreign ownership moderation variable (KA). The objects in this study are companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The data analysis method used in this research is Panel Data Regression and Moderate Regression Analysis (MRA). Hypothesis testing was carried out partially and simultaneously using the F Test and T Test. The technique used in this study to take samples was purposive sampling with a sample of 27 companies for the 2019-2021 period within 3 years. The results of this study draw the conclusion that carbon emission disclosure proxied by GRI with control variables company size (Ln), profitability (ROA) and leverage (DER) have a simultaneous effect on firm value, then the conclusion obtained after moderation is that it does not have simultaneous influence on firm value after being moderated by foreign ownership. Carbon emission disclosure with control variables company size (Ln), profitability (ROA) and leverage (DER) partially have no effect on firm value both before moderation and after moderation. From the results of the research that has been done, the researcher provides suggestions for future research to add a period of years, increase the number of samples and modify other variables. Then for companies to be able to pay attention to and increase the value of the company to get maximum profits, and finally for investors to pay attention to decisions in making investments.